Diagrammatic Representation and Inference 7th International Conference, Diagrams 2012, Canterbury, UK, July 2-6, 2012, Proceedings - Cox, Philip T.; Plimmer, Beryl; Rodgers, Peter (Lecture Notes in Artificial Intelligence, 2012)
This book constitutes the refereed proceedings of the 7th International Conference on Theory and Application of Diagrams, Diagrams 2012, held in Canaterbury, UK, in July 2012. The 16 long papers, 6 short papers and 21 poster abstracts presented were carefully reviewed and selected from 83 submissions. The papers are organized in keynotes, tutorial, workshops, graduate student symposium and topical sections on psychological and cognitive issues, diagram layout, diagrams and data analysis, Venn and Euler diagrams, reasoning with diagrams, investigating aesthetics, applications of diagrams.